Sagittal lumbo-pelvic alignment in the sitting position of elderly persons - Suzuki, Hidekazu; Endo, Kenji; Mizuochi, Jun; Murata, Kazuma; Nishimura, Hirosuke; Matsuoka, Yuji; Tanaka, Hidetoshi; Yamamoto, Kengo; Tateiwa, Toshiyuki (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2016)
In elderly persons, the sitting position in daily life is very important due to the weakness in locomotion. In previous studies, sagittal spinal alignment was mainly analyzed in the standing position. However, in order to study the sagittal spinal alignment of elderly persons, the estimation of spinal alignment in the sitting posture is also important. We proposed that there is a characteristic spinal alignment in elderly persons in the sitting position. The purpose of this study was to evaluate the sagittal lumbo-pelvic alignment in the standing and sitting positions in elderly persons. This study included 73 young adult subjects (48 men and 25 women; age 34.4 ± 8.1 years) and 107 elderly subjects (65 men and 42 women; age 67.6 ± 8.3 years). The following radiographic parameters were determined by computer-assisted measurement: L1L5 angle (L1L5), lumbosacral angle (LSA), sacral slope (SS), pelvic tilt (PT), and pelvic incidence (PI). L1L5 decreased and the pelvis rotated posteriorly in the sitting position in both young adults and elderly persons. However, the extent of alignment difference between standing and sitting in elderly persons was nearly half that of young adults (in particular, the lumbo-pelvic junction, LSA, was smaller). Regarding the extent of correlation between aging and lumbo-pelvic alignment parameters, there were significant correlations. In elderly persons, the correlation between L1L5 and PT had a tendency to be poor in the sitting position. The elderly in the sitting position showed greater lumbar lordosis and higher sacral slope than in young adults, and the correlations among lumbo-pelvic parameters were poorer than those of young adults. Thus, when moving from sitting to standing, the lumbo-pelvic mobility in the sagittal plane is suspected to be poor in elderly persons.